Características morfofisiológicas de sementes e produção de girassol em função de boro no solo - Bonacin, Gisele A. (2009)
An experiment was carried out in order to evaluate effects of boron applied to soil on the morphophysiological characteristics of sunflower seed (achene). The experiment was installed on November 17, 2000 in an experimental area at São Paulo State University - UNESP/FCAV, Jaboticabal, SP, in an oxisoil with the sunflower variety Embrapa V122-2000. The experimental design was a completely randomized block, with five doses of boron (0, 1, 2, 3 and 4 kg ha-1) with four replications. After full bloom (80-90% of open flowers), the following characteristics were evaluated during seven weeks: length, width and thickness, seed dry mass, water concentration and content, first counting of germination, final germination and oil content. Seed yield was also evaluated. There was no significant effect of boron application on seed characteristics evaluated 49 days after full bloom, and this result was associated to the initial content of boron in the soil (0.22 mg dm-3 extracted with BaCl2 1.25 g L-1), which is considered an average value. The mean yield of seeds was 2,559 kg ha-1.